PENGARUH PENGKAYAAN ARTEMIA OLEH BEBERAPA SUMBER MINYAK TERHADAP PERTUMBUHAN LARVA KERAPU TIKUS (Cromileptes altivelis) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2018)
A research on Artemia naupli enrichment of Grace Kelly grouper, Cromileptes altivelis was conducted in order to investigasi its effects on the growth, which was reflected by the relative growth of total length amd of weight, respectively. Three different enrichments treatments i.e fish oil, corn oil and coconut oil were fed on larva for 40 days. Initial total length of the larva was about 2.010 Â± 0.2559 cm. The larva feed on Artemia naupli at density of 2-5 ind/ml. The result indicated that Artemia naupli enriched fish oil 0.1 g/100 ml water en able to of brain volume, relative growth of total length and relative growth of weight better (p